Cervical cancer screening among incarcerated women - Kelly, Patricia J. (PLoS One, 2018)
BACKGROUND: Women with a history of incarceration bear a disproportionate burden of cervical disease and have special characteristics that affect their intent and/or ability to adhere to cervical screening and follow-up recommendations. The goal of this study was to identify factors associated with cervical cancer screening and screening outcomes among incarcerated women. METHODS: We applied a framework of predisposing factors, enabling factors and population-specific characteristics that could impact screening behaviors and outcomes for this population. We used bivariate chi-square tests and Wilcoxon signed-rank tests to analyze data previously collected from 290 incarcerated women. RESULTS: Cervical cancer screening belief score, as a predisposing factor, was associated with women who had an up-to-date Pap test and who had a cervical cancer diagnosis ever in their life. Both a sexual history containing high-risk behaviors and a history of abuse, population–specific factors, were each associated with having had an abnormal pap; mental health, incarceration, and substance use histories were each associated with having a diagnosis of cervical cancer. CONCLUSIONS: The significant differences in outcomes for these population-specific factors suggest the need for a health services approach that addresses the challenges to the cervical cancer preventive health needs of incarcerated women. IMPLICATIONS FOR PRACTICE: Providers working with vulnerable populations such as women who have been incarcerated should be aware that their risk histories have an influence on their follow-up behaviors. These women will need extra support for cervical cancer screening and follow-up care.